Simulation of operation modes of inverter hydro-generator; Mechanical Engineering, Automation and Control Systems (MEACS) - Lukutin B. V. Boris Vladimirovich; Shandarova E. B. Elena Borisovna; Muravlev I. O. Igor Olegovich; Matukhin D. L. Dmitriy Leonidovich; Makarova A. F. (2015, 2015)
Title screen